The effect of ammonium sulfate on the solubility of amino acids in water at (298.15 and 323.15) K - Ferreira, Luísa (2010)
Using the analytical gravimetric method the solubility of glycine, DL-alanine, L-isoleucine, L-threonine, and L-serine in aqueous systems of (NH4)2SO4, at (298.15 and 323.15) K, were measured for salt concentrations ranging up to 2.0 molal. In the electrolyte molality range studied the experimental observations showed that ammonium sulfate is a salting-in agent for most of the amino acids studied. Furthermore, the change of the relative solubility with electrolyte concentration shows a maximum, which makes the representation of the data by a simple empirical correlation such as the Setschenow equation difficult. For the development and evaluation of a robust thermodynamic framework that makes it possible to more profoundly understand aqueous amino acid solutions with ammonium sulfate additional experimental information is needed.